2017
DOI: 10.1038/cddis.2017.230
|View full text |Cite
|
Sign up to set email alerts
|

RGD-modified oncolytic adenovirus-harboring shPKM2 exhibits a potent cytotoxic effect in pancreatic cancer via autophagy inhibition and apoptosis promotion

Abstract: The M2 isoform of pyruvate kinase (PKM2) is a key driver of glycolysis in cancer cells and has critical ‘non-metabolic’ functions in some cancers; however, the role of PKM2 in pancreatic cancer remains unclear. The aim of the current study was to elucidate the role of PKM2 in pancreatic cancer progression and the potential of PKM2 as a therapeutic target. In this study, we observed that PKM2 is highly expressed in patients with pancreatic cancer and is correlated to survival. Elevated PKM2 expression promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Apoptosis is the classic mechanism by which chemotherapy agents induce cell death; 11 however, numerous studies have shown that these drugs also induce autophagy. 12 Autophagy is usually considered to be a critical process by which cells recycle ineffectual cellular components to maintain homeostasis. This process plays a critical role in programmed cell death type II, which can be exploited to suppress tumour growth.…”
mentioning
confidence: 99%
“…Apoptosis is the classic mechanism by which chemotherapy agents induce cell death; 11 however, numerous studies have shown that these drugs also induce autophagy. 12 Autophagy is usually considered to be a critical process by which cells recycle ineffectual cellular components to maintain homeostasis. This process plays a critical role in programmed cell death type II, which can be exploited to suppress tumour growth.…”
mentioning
confidence: 99%
“…The results revealed that autophagy activator rapamycin reversed the inhibiting effect on cell proliferation caused by PKM2 knockdown, while autophagy inhibitor 3-MA rescued the inducement of cell proliferation caused by PKM2 overexpression. Pioneer studies demonstrated that PKM2 knockdown caused impairment of the autophagic process, and consequently inhibited pancreatic cancer cell growth 41 . Based on the aforementioned results, we further investigate whether Beclin-1 is involved in PKM2-mediated autophagic cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor volume of the six mice in each group was measured every three days and estimated using the following equation: (length × width2)/2 [12,13]. At the end of the experiment, mice were killed and the tumors were resected for H&E staining and immunofluorescence staining analyses [14, 15, 16].…”
Section: Methodsmentioning
confidence: 99%